Lipophilic conformationally constrained spiro carbocyclic 2, 6‐diketopiperazine‐1‐acetohydroxamic acid analogues as trypanocidal and leishmanicidal agents: An extended SAR study. (18th September 2017) - Zoidis, Grigoris; Tsotinis, Andrew; Tsatsaroni, Alexandra; Taylor, Martin C.; Kelly, John M.; Efstathiou, Antonia; Smirlis, Despina; Fytas, George
Abstract : We have previously described a number of lipophilic conformationally constrained spiro carbocyclic 2, 6‐diketopiperazine (2, 6‐DKP)‐1‐acetohydroxamic acids as potent antitrypanosomal agents. In this report, we extend the SAR analysis in this class of compounds with respect to in vitro growth inhibition of Trypanosoma and Leishmania parasites. Introduction of bulky hydrophobic substituents at the vicinal position of the basic nitrogen atom in the spiro carbocyclic 2, 6‐DKP ring system can provide analogues which are potently active against bloodstream form Trypanosoma brucei and exhibit significant activities toward Trypanosoma cruzi epimastogotes and Leishmania infantum promastigotes and intracellular amastigotes. In particular, compounds possessing a benzyl or 4‐chlorobenzyl substituent were found to be the most active growth inhibitors, with activities in the low nanomolar and low micromolar ranges for T. brucei and L. infantum, respectively. The benzyl‐substituted ( S )‐enantiomer was the most potent derivative against T. brucei (IC50  = 6.8 nm ), T. cruzi (IC50  = 0.21 μm ), and L. infantum promastigotes (IC50  = 2.67 μm ) and intracellular amastigotes (IC50  = 2.60 μm ). Moreover, the ( R )‐chiral benzyl‐substituted derivative and its racemic counterpart displayed significant activities against L. donovani . Importantly, the active compounds show high selectivity in comparison with two mammalian cell lines. Abstract : The present work has extended the structure–activity relationships of spiro carbocyclic 2, 6‐DKP‐1‐acetohydroxamic acids in determining in vitro growth inhibition of trypanosomal and leishmanial parasites. Our studies demonstrate that the antiparasitic activity of this class of compounds is greatly dependent upon the alkyl or the arylalkyl substitution on either the basic nitrogen atom (N‐methylation) or at its vicinal position (C‐alkylation or arylmethylation) in the spiro carbocyclic 2, 6‐DKP skeleton.